SOFTWARE AUDIT SYSTEM - NIgam, Gaurav Kumar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
To remotely monitor your computer over the internet, you have to install this software on the remote computer (called as server) as well as on your own computer (called as client). When connected , Software Audit System software gives you the full mouse and keyboard control over your computer and you can see the whole screen of the remote PC on your own desktop. As we know that computer networks within companies and organizations become more extensive and more complex, there is a considerable growth in the number of software programs that are installed and used on the computer systems. In order to increase the reliability and efficiency of computer Systems, it is mandatory that we clearly understand and control all the computer programs that are being used. The problem may also arise when people installing unauthorized or copied computer programs on their Desktop PC’s. It is necessary that we provide auditing tools that can facilitate audit data either locally or reside on to a central network manager and it gives the information related to the installed and used computer programs